Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) untuk Meningkatkan Hasil Belajar Kimia Topik Laju Reaksi di Madrasah Aliyah Negeri 1 Pekanbaru - Asmiwati Asmiwati (Tasnim Journal for Community Service, 2022)
This research is a Class Action Research with two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The study was conducted on 32 students of class XI IPA at MAN 1 Pekanbaru. Techniques used in collecting data include tests and observation of student activities. The results showed that the application of the TAI type of cooperative learning model could improve student learning outcomes. This is evidenced by an increase in student learning outcomes and student activity from cycle I to cycle II, namely the value of learning outcomes on the final test and student activity in cycle I is 80% of students scored 78 and the average value of student activity is 1.9, while in the final test and student activity in cycle II were 90% of students scored 78 and the average value of student activity was 2.7. This shows an increase in student learning outcomes and activeness by using the TAI type of cooperative learning model.